2001
DOI: 10.1590/s0034-89102001000500008
|View full text |Cite
|
Sign up to set email alerts
|

Emergência de Aedes albopictus em recipientes artificiais

Abstract: Pesquisa subvencionada pela Fapesp (Processos Temáticos n. 95/0381-4 e n. 99/10517-1). Resumo ObjetivoEstimar o potencial de emergência média diária de adultos fêmeas de Aedes albopictus, espécie que, embora não tenha sido incriminada, até o momento, como vetora de dengue no Brasil, é muito próxima de Aedes aegypti. Métodos As observações foram realizadas quinzenalmente e de maneira ininterrupta na localidade de Pedrinhas, Estado de São Paulo, no período de 1996 a 2000. Para estimar a produtividade dos criado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Many studies that employed entomological surveys 22,23,26,29,[37][38][39] have shown higher values of infestation of eggs, larvae and vectors in the rainy period; however, the positive breeding sites persist in the drought period, a fact that is favored by the mosquito's facility to adapt to the human environment, through natural and/or artificial reservoirs 31,34,40,41 . The rainfall data referring to the months of highest number of notification of cases showed a slight relationship among one another.…”
Section: Rainfallmentioning
confidence: 99%
“…Many studies that employed entomological surveys 22,23,26,29,[37][38][39] have shown higher values of infestation of eggs, larvae and vectors in the rainy period; however, the positive breeding sites persist in the drought period, a fact that is favored by the mosquito's facility to adapt to the human environment, through natural and/or artificial reservoirs 31,34,40,41 . The rainfall data referring to the months of highest number of notification of cases showed a slight relationship among one another.…”
Section: Rainfallmentioning
confidence: 99%
“…In these less-urban areas, animals (particularly horses) are abundant and it is not uncommon to find buckets and barrels used as troughs. In the district of Pedrinhas, Ilha Comprida municipality (São Paulo State), Forattini et al (2001) estimated the potential emergence of permanent large-scale Ae. albopictus breeding sites and suggested that organic matter in these sites may influence the emergence of adult mosquitoes.…”
Section: Aedes Scapularismentioning
confidence: 99%
“…The RSP marked important moments of the path of dengue in Brazil, with articles describing a history of Aedes aegypti control programs in Brazil 154 , commenting on the introduction of Aedes albopictus in the Country and its potential impacts 71 , the first epidemics in medium cities of the Southeast region 136 , important studies on the vector behavior 111 , seroprevalence surveys in Brazilian capitals 168 as well as socioeconomic characteristics and their relation with the vector density and the occurrence of dengue 61 , 117 . Finally, in recent years, we have an article commenting on the obstacles and challenges to the development of a vaccine against dengue 1 .…”
Section: Emerging and Reemerging Diseasesmentioning
confidence: 99%